Time and Space in Tzeltal: Is the Future Uphill? - Brown, Penelope (Frontiers in Psychology, 2012)
Linguistic expressions of time often draw on spatial language, which raises the question of whether cultural specificity in spatial language and cognition is reflected in thinking about time. In the Mayan language Tzeltal, spatial language relies heavily on an absolute frame of reference utilizing the overall slope of the land, distinguishing an “uphill/downhill” axis oriented from south to north, and an orthogonal “crossways” axis (sunrise-set) on the basis of which objects at all scales are located. Does this absolute system for calculating spatial relations carry over into construals of temporal relations? This question was explored in a study where Tzeltal consultants produced temporal expressions and performed two different non-linguistic temporal ordering tasks. The results show that at least five distinct schemata for conceptualizing time underlie Tzeltal linguistic expressions: (i) deictic ego-centered time, (ii) time as an ordered sequence (e.g., “first”/“later”), (iii) cyclic time (times of the day, seasons), (iv) time as spatial extension or location (e.g., “entering/exiting July”), and (v) a time vector extending uphillwards into the future. The non-linguistic task results showed that the “time moves uphillwards” metaphor, based on the absolute frame of reference prevalent in Tzeltal spatial language and thinking and important as well in the linguistic expressions for time, is not strongly reflected in responses on these tasks. It is argued that systematic and consistent use of spatial language in an absolute frame of reference does not necessarily transfer to consistent absolute time conceptualization in non-linguistic tasks; time appears to be more open to alternative construals.